Impact of the special program for the arts on the skills of its graduates - Lopez, Carlos G. (2009)
The study determined the impact of the Special Program for the Arts on life skills areas - namely artistic skills, personal responsibility, family life, social skills, career planning and income generation abilities - of its graduates from 2004 to 2007. Survey and interview were used to gather data. Results indicate that the SPA only had an average impact on the first five life skills areas. It had minimal amount on the income generation abilities. Results from the interview suggest that SPA still had a valuable contribution; it helped its graduates in managing life's day-to-day demands and responsibilities.